Supply-demand bilateral energy structure optimization and carbon emission reduction in Shandong rural areas based on long-range energy alternatives planning model - Wang, Jing; Liu, Mohan (Frontiers in Environmental Science, 2022)
To solve the problem of large carbon emissions in rural area, this paper conducts field research in rural areas of Shandong and embarks on supply-demand bilateral energy structure optimization which combines local resource endowments, the latest rural energy application technologies and energy consumption preference. The study uses long-range energy alternatives planning (LEAP) model to analyze the trend of energy consumption and CO2 emission from 2020 to 2050 under four different scenarios. The results of Tanzhuang show that residents in rural areas still rely on traditional biomass for energy consumption, especially for winter heating. Energy structure optimization has a significant impact on energy saving and emission reduction. Energy consumption and generation are projected steadily up to 2050 under all scenarios while the carbon emissions show a downward trend with a rapid decline from 2021 to 2030 and a relatively stable state for the next 20 years. Combining policy advancement and marginal carbon abatement cost (MACC) of different energy technologies, energy structure optimization-low cost (ESO-LOW) scenario shows a higher emission reduction benefits than the others. Six other villages in Shandong are analyzed in order to demonstrate the effectiveness of supply-demand bilateral energy structure optimization, sensitivity results show that the optimization is significant to the carbon neutrality target and carbon emission reduction.